2019
DOI: 10.19044/esj.2019.v15n30p301
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation Hydrogéochimique des Aquifères du Bassin de Timia (Massif de l’Aïr, Nord du Niger)

Abstract: The Timia Basin is located in the Aïr Massif (Northern Niger). In this area, water resources are represented by altered and fissured basement and alluvial aquifers. These aquifers, are solicited for the water supply, and irrigation. These activities have for consequences the degradation of the quality of these waters. The objective of this study is to determine the physicochemical characteristics and the mechanisms house control the mineralization of groundwater in Timia area. The methodology based on hydroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The majority of these waters are very weakly mineralised. Other studies have concluded that the acquisition of groundwater mineralization is due to surface water inflow by infiltration (Alhassane et al, 2019). Moreover, the strong correlations between nitrates ( 3 NO − ), nitrites ( 2 NO − ) and EC (r > 0.90) show a strong influence of this phenomenon in the acquisition of mineralisation.…”
Section: Discussionmentioning
confidence: 86%
“…The majority of these waters are very weakly mineralised. Other studies have concluded that the acquisition of groundwater mineralization is due to surface water inflow by infiltration (Alhassane et al, 2019). Moreover, the strong correlations between nitrates ( 3 NO − ), nitrites ( 2 NO − ) and EC (r > 0.90) show a strong influence of this phenomenon in the acquisition of mineralisation.…”
Section: Discussionmentioning
confidence: 86%